Pengaruh Penambahan Fermentasi Tepung Bungkil Inti Sawit terhadap Kinerja Pertumbuhan dan Pemanfaatan Pakan Ikan Nila (Oreochromis niloticus) - Ratna Sri Devy; Heru Kusdianto; Mohamad Ma’ruf; Nurhalisa; Retno Wulandari (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2026)
Feed is an important factor in the growth of tilapia (Oreochromis niloticus). However, the high price of feed is a major obstacle for farmers. This study aims to analyze the effect of palm kernel meal fermented with commercial microorganisms (EM4) and Aquaenzyme at different doses on feed nutrient content and growth performance. The design used a completely randomized design (CRD), with 3 treatments and 4 replicates: P0 (control, without EM4 or Aquaenzyme), P1 (palm kernel meal fermented for 24 hours using EM4 at a dose of 8 ml/kg palm kernel meal), and P2 (palm kernel meal fermented for 24 hours using Aquaenzyme at a dose of 8 g/kg palm kernel meal). Feeding was given 3 times (08.00, 12.00, and 17.00 WITA), with a maintenance period of 40 days. The ANOVA results showed that fermentation had a significant effect (P<0.05) on absolute weight gain, daily specific growth rate, and feed conversion. P2 (palm kernel meal fermented for 24 hours using Aquaenzym at a dose of 8g/kg palm kernel meal) was the best treatment, with a protein content of 41.26%, fat 9.43%, BETN 25.95%, and crude fiber 2.99%, resulting in the highest absolute growth (g), specific growth rate (%/day), total length growth (cm) of 76.08 ± 3.12, 1.52 ± 0.27, 14.10 ± 5.36, and the lowest feed conversion (g) of 1.02 ± 0.34.